Teddy at the throttle - Swanson, Gloria, 1897-1983 (Academic Video Online, 2014)
Villain Beery, in a plot to get his hands on a fortune, ties Gloria to the railroad tracks and Bobby must rescue her with a major assist from canine pal Teddy. Locations include the Beverly Hills Hotel at Sunset Blvd. and Beverly Drive; Chatsworth Park train pass; and Pacific Electric railroad trestle near Fletcher Drive and Riverside Drive on the Glendale line.